1998
DOI: 10.1139/x98-028
|View full text |Cite
|
Sign up to set email alerts
|

Chronology development and climate response analysis of different New Zealand pink pine (Halocarpus biformis) tree-ring parameters

Abstract: Seven different tree-ring parameters (total ring width, earlywood width, latewood width, maximum latewood density, minimum earlywood density, average earlywood density, and average latewood density) were obtained from pink pine (Halocarpus biformis Hook.) at one chronology site in New Zealand (NZ). The chronologies were analyzed individually and then compared with each other. The relationships between the different tree-ring parameters and climate data (NZ average and local climate data) are also presented. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…The MXD indices exhibit low year-to-year variability, as emphasized by the low mean sensitivities (0.072-0.074) and the standard deviations (0.075-0.080). These low values of MXD were found in the previous reports (Schweingruber et al 1978;Cleaveland 1986;Xiong et al 1998). In general,…”
Section: The Characteristics Of Tree-ring Chronologiessupporting
confidence: 69%
See 1 more Smart Citation
“…The MXD indices exhibit low year-to-year variability, as emphasized by the low mean sensitivities (0.072-0.074) and the standard deviations (0.075-0.080). These low values of MXD were found in the previous reports (Schweingruber et al 1978;Cleaveland 1986;Xiong et al 1998). In general,…”
Section: The Characteristics Of Tree-ring Chronologiessupporting
confidence: 69%
“…The climate of the early part of growing season also has a significant impact on the formation of MXD. Previous studies (Schweingruber et al 1978;Cleaveland 1986;Xiong et al 1998;D'Arrigo et al 2004;Büntgen et al 2008;Fan et al 2009) also demonstrated the responses of MXD to the warm season temperatures (from spring to late summer). Elevation is also an important factor limiting the growing season length.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is observed that earlywood density parameters are the major contributor in dendroclimatic estimation in this study. The results of our analysis are similar to some studies (Xiong et al, 1998;Pant et al, 2000) demonstrated that earlywood tree-ring parameters (earlywood density, minimum density, and earlywood width) were also sensitive to climate. Climate may strongly influence all types of tree-ring data (total ring width, early and latewood width, early and latewood density) depending on species and site conditions.…”
Section: Assessment Of Potential For Climate Reconstructionsupporting
confidence: 90%
“…The results indicate there is strong climatic information in the LWD standard chronology. Some investigators (Polge, 1970;Parker and Henoch, 1971;Schweingruber et al, 1978;Briffa et al, 1988;Xiong et al, 1998;Büntgen et al, 2008;Wang et al, 2009) found that the tree-ring density parameters had lower MS and SD compared with tree-ring width parameters. Mean sensitivity and standard deviation of the LWD standard chronology is also low.…”
Section: Discussionmentioning
confidence: 99%
“…The seven tree-ring parameters (ring width, earlywood width, latewood width, maximum density, minimum density, mean earlywood density, mean latewood density) were measured for each annual ring on each sample. The boundary between earlywood and latewood was identified as the mid-point between the maximum and minimum density measurements of each ring (Xiong et al, 1998). The crossdated tree-ring sequences were quality checked by the COFECHA program (Holmes, 1983).…”
Section: Sampling and Chronology Developmentmentioning
confidence: 99%